A Key Role for Apoplastic H2O2 in Norway Spruce Phenolic Metabolism. Issue 3 (18th May 2017) - Laitinen, Teresa; Morreel, Kris; Delhomme, Nicolas; Gauthier, Adrien; Schiffthaler, Bastian; Nickolov, Kaloian; Brader, Günter; Lim, Kean-Jin; Teeri, Teemu H.; Street, Nathaniel R.; Boerjan, Wout; Kärkönen, Anna
Abstract : The redox state of the apoplast has a profound influence on cellular metabolism. Abstract: Apoplastic events such as monolignol oxidation and lignin polymerization are difficult to study in intact trees. To investigate the role of apoplastic hydrogen peroxide (H2 O2 ) in gymnosperm phenolic metabolism, an extracellular lignin-forming cell culture of Norway spruce ( Picea abies ) was used as a research model. Scavenging of apoplastic H2 O2 by potassium iodide repressed lignin formation, in line with peroxidases activating monolignols for lignin polymerization. Time-course analyses coupled to candidate substrate-product pair network propagation revealed differential accumulation of low-molecular-weight phenolics, including (glycosylated) oligolignols, (glycosylated) flavonoids, and proanthocyanidins, in lignin-forming and H2 O2 -scavenging cultures and supported that monolignols are oxidatively coupled not only in the cell wall but also in the cytoplasm, where they are coupled to other monolignols and proanthocyanidins. Dilignol glycoconjugates with reduced structures were found in the culture medium, suggesting that cells are able to transport glycosylated dilignols to the apoplast. Transcriptomic analyses revealed that scavenging of apoplastic H2 O2 resulted in remodulation of the transcriptome, with reduced carbon flux into the shikimate pathway propagating down to monolignol biosynthesis. Aggregated coexpression network analysis identified candidate enzymes and transcription factors for monolignol oxidation and apoplastic H2 O2 production in addition to potential H2 O2 receptors. The results presented indicate that the redox state of the apoplast has a profound influence on cellular metabolism.